Brief review: investigation of the cinnamomum genus’s potential for managing diabetes - Yasri, Budi; Riyanti, Soraya (Gema Wiralodra, 2023)
Ethnopharmacological research is an approach to exploring the local knowledge of specific communities regarding the use of medicinal plants. This article discusses the use of cinnamon (Cinnamomum) as an effective alternative medicine in several regions in Indonesia. The method used is data collection through searching for literature published in scientific research articles and journals. A literature search was conducted using search engines posted on several sites, such as Google Scholar, Pubmed, and Science Direct. Based on the review conducted, it can be concluded that the Cinnamomum genus is widely used by various ethnic groups in Indonesia as a natural ingredient to help control blood glucose levels and is used as an alternative supplement for diabetes mellitus sufferers. Among the species from the Cinnamomum genus that have the potential to help prevent blood glucose levels are Cinnamomum burmanii, Cinnamomum verum, Cinnamomum tamala, and Cinnamomum zeylanicum.